'Architectural literacy': Functions of architectural drawing. Issue 1 (1st April 2021) - Schaeverbeke, Robin; Aarts, Hélène
'Literacy' refers to the ability to both assign meaning to ‐ and to create messages. Transposing this concept to 'architectural literacy' could refer to the assigning of meaning to architectural messages and the ability to create such messages. 'Architectural literacy' suggests that architects employ a distinct language to communicate, process and design spatial propositions and that the knowledge of such literacy could be of importance to a broader community. In architectural practices, drawing is used to discourse about forms and spaces. Our approach to disassemble architectural drawings in a set of functions, aims to add understanding about a specific ability to learn and understand architecture. Disassembling architectural drawing in a set of functions stems from a reflective conversation upon our practices as drawing teachers in architectural faculties. In an attempt to (re)structure the didactic foundations of our own teaching practices, we started discussing the kind of drawings architects resort to. This research gradually revealed a set of distinct, yet interrelated functions and activities. We introduce architectural drawing as a specific faculty of a large field of drawing practices, which revolves around the convergence of perception, imagination, disclosure and artistic expression. Learning about the distinct activities and abilities to process forms and spaces provides a knowledge base to explore foundations of architectural reasoning.